On Suzuki and Wardowski-Type Contraction Multivalued Mappings in Partial Symmetric Spaces. (11th June 2021) - Asim, Mohammad; Aydi, Hassen; Imdad, Mohammad
Abstract : The purpose of this paper is to provide some fixed-point results for Suzuki and Wardowski-type contraction multivalued mappings in partial symmetric spaces. We give some examples to support and substantiate the developed notions and obtained results. Also, we use one of our main results to establish the existence and uniqueness of the solution for a system of integral inclusions.